Re-reading the dossier about the Venetian prototypographers Johann and Wendelin from Spira - Edoardo Barbieri (JLIS.it, 2021)
The known documentation about the brothers John and Windelin from Spira is reread here. This is above all informations obtained from the editions themselves, in addition to the famous privilege for the exclusive exercise of the printing in Venice. The occasion is gluttonous to highlight some respectable female figures in the family entourage of the from Spira, as well as the rich plot of German merchants underlying the landing of the typography in the lagoon (John from Köln, the Dinslakens, Peter Ugelheimer). In addition, it is thus possible to identify the proprium that characterized the production of Vindelino, whose slightly elusive figure usually seems to disappear in the face of his brother’s pre-eminence.